Information Schools: Current panorama, trends and proposals - López-Borrull, Alexandre; Cobarsí-Morales, Josep (Anuario ThinkEPI, 2017)
An overview of the iSchools movement and its evolution in recent years is presented. Its growth at a global level is described, stating that the number of centers outside the United States has surpassed the number inside. Perspectives of growth are analyzed. Continental chapters have been created, and the European one is described. Considering that, at present, there are 6 Iberian iSchools, some future possibilities for collaboration are suggested.
Keywords: iSchools; UOC; UC3M; UPV; iCaucus; Universities; United States; Iberia; Spain.